2015
DOI: 10.1055/s-0034-1398688
|View full text |Cite
|
Sign up to set email alerts
|

Selective Endothelin-B Receptor Stimulation Increases Vascular Endothelial Growth Factor in the Rat Brain during Postnatal Development

Abstract: Endothelin, vascular endothelial growth factor and nerve growth factor play important roles in development of the central nervous system. ET(B) receptors have been shown to promote neurovascular remodeling in the adult ischemic brain through an increase in VEGF and NGF. It is possible that ET(B) receptors may be involved in postnatal development of the brain through VEGF and NGF. In the present study, the brains of male rat pups on postnatal days 1, 7, 14 and 28 were analyzed for expression of ET(B) receptors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…Subsequently, by administration of an ET B agonist in an adult rat stroke model, Leonard et al [22] identified a relationship whereby ET B receptor expression and stimulation enhance vascular endothelial growth factor (VEGF) and neuronal growth factor (NGF) supporting neurovascular remodeling. However, pharmacological stimulation of ET B receptors during postnatal development of normal rats produced an increase in only VEGF with no change in NGF expression in the brain [19] . During CNS development, there is a natural process of establishing a complex network of neurons which involves a nonpathological process of neuronal cell death prenatally resulting in loss of about 50% of the neurons and then elimination of about 50% unwarranted connections between neurons postnatally [23,24] .…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Subsequently, by administration of an ET B agonist in an adult rat stroke model, Leonard et al [22] identified a relationship whereby ET B receptor expression and stimulation enhance vascular endothelial growth factor (VEGF) and neuronal growth factor (NGF) supporting neurovascular remodeling. However, pharmacological stimulation of ET B receptors during postnatal development of normal rats produced an increase in only VEGF with no change in NGF expression in the brain [19] . During CNS development, there is a natural process of establishing a complex network of neurons which involves a nonpathological process of neuronal cell death prenatally resulting in loss of about 50% of the neurons and then elimination of about 50% unwarranted connections between neurons postnatally [23,24] .…”
Section: Introductionmentioning
confidence: 88%
“…β-Tubulin (1: 2,000; Cell Signaling Technology) or β-actin (1: 10,000; SigmaAldrich) were used as loading controls. The dilutions for all antibodies were determined based on previous studies in our laboratory [19,30,31] using the same antibodies as well as literature provided by the manufacturer. The blots were then visualized with SuperSignal West Pico Chemiluminescent Substrate (Thermo Scientific) using the Kodak Gel Logic 1500 Imaging System (Carestream Health Inc., New Haven, CT, USA).…”
Section: Determination Of Cb 1 and Et B Receptors Vegf And Ngf Exprmentioning
confidence: 99%
See 3 more Smart Citations